1993
DOI: 10.1143/jjap.32.l233
|View full text |Cite
|
Sign up to set email alerts
|

P-Type ZnSe:N Prepared by Electron Cyclotron Resonance Radical Beam Doping during Molecular Beam Epitaxial Growth

Abstract: ZnSe doped with nitrogen(N) has been prepared by molecular beam epitaxy using N2 *, N* nitrogen radicals, N2 + ions and N atoms from an electron cyclotron resonance nitrogen plasma source. N-doped ZnSe/GaAs heteroepitaxial layers showed p-type conduction with net acceptor concentrations as high as 1.8×1018 cm-3, and the activation rate of N atoms was 60%. Photoluminescence spectra measured at 7 K from p-type ZnSe:N layers with net acceptor concentrations higher than 1018 cm-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It is easy to identify the voltage V m since it coincides with the maximum differential current ͑dI/dV͒ in the I-V characteristics. 7,8 From this discussion, we can deduce that the removed nitrogen atoms are almost all first-negative transitions of N 2 molecules. 4.…”
Section: Znse Nitrogen Doping Using An Ion-free Electron-cyclotron-rementioning
confidence: 76%
See 1 more Smart Citation
“…It is easy to identify the voltage V m since it coincides with the maximum differential current ͑dI/dV͒ in the I-V characteristics. 7,8 From this discussion, we can deduce that the removed nitrogen atoms are almost all first-negative transitions of N 2 molecules. 4.…”
Section: Znse Nitrogen Doping Using An Ion-free Electron-cyclotron-rementioning
confidence: 76%
“…One of the key techniques, obtaining p-type films with low resistivity was achieved by a nitrogen radical doping technique. [5][6][7][8][9] In this letter, nitrogen doping in ZnSe using a new type of ECR source is studied. The results led to the first blue-green laser room-temperature pulsed operation.…”
Section: Znse Nitrogen Doping Using An Ion-free Electron-cyclotron-rementioning
confidence: 99%
“…They respectively achieved a net acceptor concentration of 10 17 cm ±3 and 10 15 cm ±3 . The plasma can be generated using a radio frequency, [117] electron cyclotron resonance microwaves, [119] or direct current. [110] Marginal success was obtained by introducing the plasma into low-pressure OMVPE.…”
Section: Nitrogen Precursors For P-type Dopingmentioning
confidence: 99%
“…[1][2][3][4] So far, the maximum net acceptor concentration (N A ϪN D ) has been limited to around 1ϫ10 18 cm Ϫ3 in ZnSe. 1 One of the most important growth parameters is the chemical species in the nitrogen plasma: excited neutral nitrogen atoms, molecules, and nitrogen ions.…”
mentioning
confidence: 99%
“…The nitrogen plasma in a plasma cavity has previously been characterized by optical emission spectroscopy. 3,[5][6][7][8] Several of these reports suggested that nitrogen ions may degrade the crystal quality of p-ZnSe:N and reduce N A ϪN D , however, without any direct evidence. The effective chemical species have not been elucidated yet either.…”
mentioning
confidence: 99%